2021
DOI: 10.1097/icb.0000000000000790
|View full text |Cite
|
Sign up to set email alerts
|

RETINAL DYSTROPHY IN A PATIENT WITH McARDLE DISEASE

Abstract: Purpose: To report a case of pattern dystrophy in a patient with McArdle disease, a rare autosomal recessive disorder of glycogen metabolism.Methods: Case report.Results: A 29-year-old woman with a history of muscle biopsy-confirmed McArdle disease presented with fundus findings consistent with pattern dystrophy. Multimodal imaging, including optical coherence tomography and fundus autofluorescence, was performed.Conclusion: To our knowledge, this is the third reported case of pattern dystrophy in a patient wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Descriptions of extramuscular manifestations are rare; although in recent years, there have been a very small number of people with McArdle disease reported to have pattern retinal dystrophy (PRD). [12][13][14][15][16] Anecdotally, our group has observed frequent thyroid involvement in these patients and a first report has been recently made. 17 Following these observations, more attention has been paid by our team to detect possible extramuscular manifestations, with a particular interest in thyroid function and retinal abnormalities.…”
Section: Introductionmentioning
confidence: 90%
“…Descriptions of extramuscular manifestations are rare; although in recent years, there have been a very small number of people with McArdle disease reported to have pattern retinal dystrophy (PRD). [12][13][14][15][16] Anecdotally, our group has observed frequent thyroid involvement in these patients and a first report has been recently made. 17 Following these observations, more attention has been paid by our team to detect possible extramuscular manifestations, with a particular interest in thyroid function and retinal abnormalities.…”
Section: Introductionmentioning
confidence: 90%
“…So far, no experimental data explain the exact role of PYGM in this process. However, it is known that retinopathy can be one of the symptoms in muscle glycogen phosphorylase deficiency (McArdle disease) [ 29 , 36 , 37 , 38 ]. Analysis of the PYGM expression pattern leads to the conclusion that impaired glycogen metabolism, both in the retinal pigment epithelium and in cone photoreceptors, is involved in McArdle disease-linked retinopathy [ 29 ].…”
Section: The Biological Importance Of Pygmmentioning
confidence: 99%
“…Several case reports and longitudinal case studies have confirmed that retinopathy is an additional clinical phenotype feature associated with McArdle disease [ 29 , 36 , 37 , 38 , 49 ]. In the case of McArdle patients, the lack of PYGM may impair the ability of retinal pigment epithelium and cone photoreceptors to obtain sufficient energy, which may further lead to pathological changes [ 29 ].…”
Section: The Biological Importance Of Pygmmentioning
confidence: 99%
“…Although PYGM expression still needs to be measured in these cells, four McArdle disease case reports with RPE dystrophy may indicate that this dystrophy can be related to PYGM mutations. Further, genetic screenings have demonstrated that these patients present mutations in the PYGM gene and not in the known dystrophy-causing genes, thus showing a possible relationship between retinopathy and McArdle disease [51,52].…”
Section: Pygm Expression In Other Tissuesmentioning
confidence: 99%